Oral vancomycin prophylaxis for the prevention of Clostridium difficile infection: A systematic review and meta-analysis. (29th November 2020) - Babar, Sumbal; El Kurdi, Bara; El Iskandarani, Mahmoud; Haddad, Ibrahim; Imam, Zaid; Alomari, Mohammad; Myers, James; Moorman, Jonathan
Abstract: Objective: Recently, oral vancomycin prophylaxis (OVP) has been suggested for the prevention of Clostridium difficile infection (CDI). We conducted a systematic review and meta-analysis to investigate the efficacy and safety of this approach. Design: Systematic review and meta-analysis. Methods: We conducted a computerized search of MEDLINE, EMBASE, and Cochrane databases from inception to March 2019 for publications investigating OVP for CDI prevention. Results were screened for eligibility. Relevant data were extracted and analyzed. Publication bias was assessed using the Egger test. Results: Ultimately, 8 retrospective studies and 1 prospective study examining 2174 patients, published between 2016 and 2019 were included in the review. OVP was associated with decreased CDI (odds ratio, 0.263; 95% confidence interval, 0.13–0.52) with considerable heterogeneity (I 2 = 61%). Meta-regression showed that total daily dose of OVP correlated with CDI, explaining 100% of heterogeneity between studies. Furthermore, 3 studies evaluated the risk of vancomycin-resistant enterococci (VRE) infection after OVP and found no significant increase. Conclusion: Our results suggest that OVP might decrease CDI rates in at-risk populations, although this conclusion should be interpreted with caution. Higher daily doses of OVP might increase CDI. Although the use of OVP in high-risk patients may reduce CDI, this suggestion has yet to be validated by prospective blinded randomized controlled trials.